Pengembangan Petunjuk Praktium IPA Alternatif Berpendekatan Saintifik untuk Meningkatkan Kemampuan Berpikir Kritis Siswa SMP - Mulia Rasyidi; Muhsinun Muhsinun (Jurnal Ilmiah Wahana Pendidikan, 2020)
Learning in schools is influenced by the development of the applicable curriculum. Currently education in Indonesia applies the 2013 curriculum which uses a scientific approach. His special interest in science subjects at SMP One of the supporters of the realization of a good learning process is to use the media practicum manuals, but often science practicum manuals use tools and materials that cannot be reached by the school so that practicum activities are not carried out optimally. Therefore it is necessary to develop alternative science practical instructions with a scientific approach that can facilitate learning in schools, especially in science subjects. The purpose of this study was to determine the feasibility and effectiveness of alternative science practical instructions with a scientific approach on critical thinking skills. This research is a Research and Development research. The results showed that the alternative science practicum guidelines developed were feasible and effective for students' critical thinking skills. This can be seen from the average score of the acquisition of the validation assessment from expert validation reaching 71.21 valid with good criteria, an increase in students' critical thinking skills using the N-Gain formula of 0.72. Based on the data and research results, it can be concluded that the alternative science practicum instructions with a scientific approach are feasible and effective for students' critical thinking skills